Telementoring of primary care providers delivering hepatitis C treatment in New York City: Results from Project INSPIRE. Issue 3 (10th May 2018) - Teixeira, Paul A.; Bresnahan, Marie P.; Laraque, Fabienne; Litwin, Alain H.; Shukla, Shuchin J.; Schwartz, Jonathan M.; Reynoso, Sheila; Perumalswami, Ponni V.; Weiss, Jeffrey M.; Wyatt, Brooke; Schackman, Bruce R.
Abstract: Introduction: The recent availability of highly effective, easily administered, and relatively nontoxic treatments for hepatitis C virus (HCV) infection provides an opportunity for clinicians to treat HCV in nonspecialist settings with appropriate support. Project INSPIRE provides care coordination to HCV patients and a web‐based training program (telementoring) on disease management and treatment by HCV specialists to primary care providers inexperienced in HCV treatment. Weekly telementoring sessions use a didactic and case‐based approach to instruct non‐HCV providers on how to identify and assess HCV treatment candidates and prescribe appropriate treatment. Methods: We used mixed methods to assess the telementoring service, including provider surveys and semistructured interviews. Quantitative data were analyzed using descriptive statistics, and qualitative data were analyzed to identify dominant themes. Results: Provider survey responses indicated an increased ability to identify and evaluate HCV treatment candidates and increased confidence in sharing knowledge with peers and patients. Interviews revealed a high degree of satisfaction with the telementoring service and Project INSPIRE overall. The telementoring service was viewed as having enhanced providers' knowledge, confidence, and ability to treat their own HCV‐infected patients rather than having to refer them to an HCV specialist with resulting benefits for continuity of care. Providers reported comradery and collegiality with other INSPIRE providers and satisfaction with professional growth from attaining new knowledge and skills via the telementoring service. Conclusions: Using readily available web conferencing technology, telementoring can facilitate knowledge transfer between specialists and primary care providers, facilitating continuity of care for patients and increased provider satisfaction.